The Contribution of the Crystalline Lens to Chromatic and Spherical Aberrations of the Eye - Sivak, Jacob G (Canadian Journal of Optometry, 1982)
The longitudinal chromatic aberration of the eye is greater than expected from reduced eye calculations. Recent evidence shows that this is due to the fact that chromatic dispersion of the crystalline lens is greater than previous estimates, particularly at wavelengths below 500 nm. Measurements of spherical aberration of the lens indicate that the aberration is almost absent. Since the eye is known to be quite free of spherical aberration, both the cornea and the lens may be considered to have relatively constant focal lengths for incident light rays of varying separations.